Management of resources in multiunit construction projects with the use of a tabu search algorithm. Issue 2 (17th February 2017) - Podolski, Michał
Abstract: The paper presents the problem of optimal management of the resources in multiunit construction project. During the creation of the models of this kind of the project the flow-shop system is rarely used. Flow-shop system now is widely applied in modelling of industrial processes, computer systems. In the model presented in the paper flow shop system with teams of working groups is used. It allows its users to shorten the time of realization of multiunit construction projects in a significant way, because works in the project can be realized by teams of working groups of any cardinality. This is new model of multiunit construction project which has not been examined in field of scheduling of construction project yet. The presented optimization model of multiunit construction project with teams of working groups performing one type of work is NP-hard optimization problem. During the scheduling of such projects there was an artificial intelligence tool used, i.e. metaheuristic tabu search algorithm. Tabu search algorithm can provide solutions of very good quality. The paper also presents a calculation example of the above mentioned problem. The obtained in calculation example result is fully satisfactory.